A simple and robust shade correction scheme for remote sensing reflectance obtained by the skylight-blocked approach - Yu, Xiaolong; Lee, Zhongping; Shang, Zhehai; Lin, Hua; Lin, Gong (Optics express, 2021)
The skylight-blocked approach (SBA) provides a direct and high-precision measurement of the water-leaving radiance ( L w ), which allows a confident determination of the remote sensing reflectance ( R rs ), where R rs is defined as the ratio of L w to the downwelling irradiance just above the surface. However, the R rs obtained by SBA is subject to self-shading error. The present shade error correction scheme (Shang17, [ Appl. Opt. 56, 7033-7040, 2017]), implemented via spectral optimization, encounters large errors if there is a mismatch in the spectral models of the component inherent optical properties (IOPs). Following the concept of the quasi-analytical algorithm (QAA, [ Appl. Opt. 41, 5755-5772, 2002]), a novel scheme (ShadeCorr QAA ) is proposed without the need to model the component IOPs. Evaluations with numerical simulations and controlled measurements show that ShadeCorr QAA outperforms Shang17 in all water types and can correct the shade impact excellently, even for highly productive waters. ShadeCorr QAA is further improved at the chlorophyll fluorescence band, where a constructed absorption coefficient is used to estimate the shade error. Collectively, ShadeCorr QAA , with higher accuracy and broader applicability than Shang17, is recommended for the shade correction associated with SBA and other similar measurements where there is a shade impact on R rs .